Aportación a la micoflora de los Pirineos y Pre-pirineos de Cataluña. II. Algunas especies asociadas al abeto (Abies alba) - Rocabruna i Llavanera, August; Vila i Garcia, Jordi; Tabarés Carriedo, Manuel; Ballarà i Noguera, Josep (Revista Catalana de Micologia, 2007)
Contribution to the fungal nora of the Pyrenean and Pre-Pirenean areas of Catalonia. II. Sorne species associated with the fir (Abies alba). A study of 18 species collected in 1994 and 1995, under Abies alba. Each species recorded ineludes a description, iconography and rernarks. Sorne of thern are of special interest: Durandiella gallica, Perrotia flammea, Bondarzewia mesenlerica, Exidia umbrinella and Gerronema chrysophyllum.